Investigation on Range Anxiety and Safety Buffer of Battery Electric Vehicle Drivers. (13th June 2018) - Yuan, Quan; Hao, Wei; Su, Haotian; Bing, Guanwen; Gui, Xinyuan; Safikhani, Abolfazl
Abstract : Drivers tend to have more range anxiety compared with driving traditional fuel vehicles if they are driving battery electric vehicle (BEV) with a long trip. Range anxiety could potentially have negative effect on driver's emotions and behaviors. In order to understand this behavior and improve the related safety issues, this paper will focus on BEV drivers' study in China. A survey on BEV drivers' actual range anxiety as well as the effect of range anxiety on drivers' behaviors is conducted in this research. Levels of feelings and attitudes of the interviewees are quantized with Likert scales using mathematical tools of the relationship. Safety buffer is defined as a measurement of the period given range anxiety starting to significantly intervene in driver's operation. The research reveals the proportional quotative relationship between BEV drivers' safety buffer and the mileage of trip. Factors, including driving experience, satisfactory level of recharge accessibility, and resistibility to emotions, are found to be significant contributing factors to influence the perceived range anxiety level of BEV drivers. This research will provide implications to the future study on the interface design of BEV.